2000
DOI: 10.1006/viro.2000.0614
|View full text |Cite
|
Sign up to set email alerts
|

The Vaccine Origin of the 1968 Epidemic of Type 3 Poliomyelitis in Poland

Abstract: A clear association was demonstrated between the use of USOL-D-bac type 3 poliovirus live-attenuated vaccine and the 1968 poliomyelitis epidemic in Poland. The epidemic followed small-scale trials with Sabin and USOL-D-bac type 3 vaccine strains carried out in seven countries including Poland. Factors that might have contributed to the genesis and development of the epidemic were the pattern of virus excretion from vaccinees, mutations found in viruses from the epidemic, and the particular vaccination policies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Transmissibility of a live attenuated virus vaccine by mosquitoes is unacceptable because it places unvaccinated individuals at risk of infection, either by the original vaccine candidate or by more virulent derivatives created by the loss of attenuating mutations. 8,9 In the current study, 2A⌬30 demonstrated a reduced capability for infecting the midgut and for causing a disseminated infection in mosquitoes infected by artificial membrane feeding. Furthermore, 2A⌬30 was not transmitted from vaccinees to mosquitoes that were allowed to feed on the vaccinees during a period of viremia.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Transmissibility of a live attenuated virus vaccine by mosquitoes is unacceptable because it places unvaccinated individuals at risk of infection, either by the original vaccine candidate or by more virulent derivatives created by the loss of attenuating mutations. 8,9 In the current study, 2A⌬30 demonstrated a reduced capability for infecting the midgut and for causing a disseminated infection in mosquitoes infected by artificial membrane feeding. Furthermore, 2A⌬30 was not transmitted from vaccinees to mosquitoes that were allowed to feed on the vaccinees during a period of viremia.…”
Section: Discussionmentioning
confidence: 51%
“…The candidate should not be transmissible from humans to mosquitoes to prevent both the introduction of dengue virus into new environments and the loss of the attenuation phenotype that can result from sustained transmission of live virus vaccines. 8,9 Recombinant DNA technology has greatly facilitated the development of live attenuated vaccines for dengue and other flaviviruses. [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Mononucleotide and dinucleotide frequencies and codon usage were analyzed in the original reports of poliovirus genomic sequences (36,57,61,70). The mono-, di-, and trinucleotide frequency patterns are similar for the three Sabin strains (70) and appear to be conserved across poliovirus genotypes (24,35,39,42,46,78) and other human enterovirus species C serotypes (8). As with other enteroviruses, the component bases in the Sabin 2 open reading frame (ORF) are present in approximately equal proportions (24.0% U, 22.9% C, 29.9% A, and 23.1% G) (59,70), a property favorable to a low bias in codon usage (53).…”
Section: Resultsmentioning
confidence: 99%
“…However, the possibility that antigenic poliovirus variants such as strain 31043 could establish widespread infections in suboptimally vaccinated populations cannot be excluded. Low levels of protective antibodies against poliovirus in the population as a consequence of inadequate vaccination and the atypical antigenic properties of epidemic strains were identified as key factors in the establishment of outbreaks of type 3 poliomyelitis in Poland (1968) (28) and Finland (1984) (19). The outbreak in Poland involved poliovirus strains derived from the USOL-Dbac vaccine virus, which was used in a small trial.…”
Section: Discussionmentioning
confidence: 99%